Optimalisasi Peran Pemuda Melalui NTC (Ngrayun Tourism Creative) dalam Menciptakan Ekonomi Kreatif di Desa Selur Kecamatan Ngrayun Kabupaten Ponorogo - Teguh Ansori (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2018)
This study aimed to create a creative economy carried out by Youth, NTC (Ngrayun Tourism Creative) namely the management of nature as a tourist place. The method used Asset Based Community Development (ABCD) approach, where in Selur Village, Ngrayun Sub-district has beautiful natural scenery to be used as a tourist attraction, the tourist attractions were managed by youth and the people who were the members of NTC (Ngrayun Tourism Creative). The results of this study were creating employment opportunities for youth of NTC (Ngrayun Tourism Creative) who were referred in the creative economy through using of nature as a tourist place, so as to reduce unemployment in Selur Village. There were several activities in reducing unemployment, namely as the provider of parking lots, selling various food, such as Tempeh typical of Ngrayun, Klobot coffee typical of Temon Village and so on. There were several tourist attractions that were managed by NTC (Ngrayun Tourism Creative) including Watu Semaur, Siman Simak, Sunggah Waterfall, Dragon Fruit Garden, Sweets, and many more. With the existence of these activities, in the other than as creative economy, it also provided an active role for village youth in social activities. Creative economics which were generated by NTC (Ngrayun Tourism Creative) such as Janggelan Juice, Tempeh Ngrayun and Klobot Coffee.